Reconciliation of international administrative coding systems for comparison of colorectal surgery outcome. (July 2014) - Munasinghe, A.; Chang, D.; Mamidanna, R.; Middleton, S.; Joy, M.; Penninckx, F.; Darzi, A.; Livingston, E.; Faiz, O.; the GI Goal Group Dr Foster Global Comparators (GC) Project, Dr Foster Intelligence in association with the Dr Foster Unit at Imperial College London
Abstract Aim Significant variation in colorectal surgery outcomes exists between different countries. Better understanding of the sources of variable outcomes using administrative data requires alignment of differing clinical coding systems. We aimed to map similar diagnoses and procedures across administrative coding systems used in different countries. Method Administrative data were collected in a central database as part of the Global Comparators (GC) Project. In order to unify these data, a systematic translation of diagnostic and procedural codes was undertaken. Codes for colorectal diagnoses, resections, operative complications and reoperative interventions were mapped across the respective national healthcare administrative coding systems. Discharge data from January 2006 to June 2011 for patients who had undergone colorectal surgical resections were analysed to generate risk‐adjusted models for mortality, length of stay, readmissions and reoperations. Results In all, 52 544 case records were collated from 31 institutions in five countries. Mapping of all the coding systems was achieved so that diagnosis and procedures from the participant countries could be compared. Using the aligned coding systems to develop risk‐adjusted models, the 30‐day mortality rate for colorectal surgery was 3.95% (95% CI 0.86–7.54), the 30‐day readmission rate was 11.05% (5.67–17.61), the 28‐day reoperation rate was 6.13% (3.68–9.66) and the mean length of stay was 14 (7.65–46.76) days. Conclusion The linkage of international hospital administrative data that we developed enabled comparison of documented surgical outcomes between countries. This methodology may facilitate international benchmarking.